2010
DOI: 10.1098/rspb.2010.0501
|View full text |Cite
|
Sign up to set email alerts
|

Floral colour versus phylogeny in structuring subalpine flowering communities

Abstract: The relative number of seeds produced by competing species can influence the community structure; yet, traits that influence seed production, such as pollinator attraction and floral colour, have received little attention in community ecology. Here, we analyse floral colour using reflectance spectra that include near-UV and examined the phylogenetic signal of floral colour. We found that coflowering species within communities tended to be more divergent in floral colour than expected by chance. However, coflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(146 citation statements)
references
References 91 publications
8
133
2
3
Order By: Relevance
“…Of five subalpine meadows between 1500 and 1700 m elevation studied by McEwen & Vamosi (2010) in Alberta, Canada, one had a statistically significant degree of phylogenetic clustering and one showed a significant degree of floral colour diversity, but the patterns in other communities were not significantly different from random expectations. This study was exemplary in combining phylogenetic comparative analyses with spectrophotometric measurement of floral reflectance, although 'colour' was quantified by principal component analysis of the reflectance spectra without reference to any pollinator visual system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of five subalpine meadows between 1500 and 1700 m elevation studied by McEwen & Vamosi (2010) in Alberta, Canada, one had a statistically significant degree of phylogenetic clustering and one showed a significant degree of floral colour diversity, but the patterns in other communities were not significantly different from random expectations. This study was exemplary in combining phylogenetic comparative analyses with spectrophotometric measurement of floral reflectance, although 'colour' was quantified by principal component analysis of the reflectance spectra without reference to any pollinator visual system.…”
Section: Introductionmentioning
confidence: 99%
“…We used the mean pair-wise phylogenetic distance (MPD) between species in each vegetation group as the metric of structure (Webb et al 2002;McEwen & Vamosi 2010). The significance of this metric was tested by comparison to a null distribution derived from 10 000 random permutations (ii) Phylogenetic signal for floral colour…”
Section: A T a A N A L Y S I S (I) Phylogenetic Structure Within Almentioning
confidence: 99%
“…Enhanced discrimination by pollinators could benefit plants as well, if it increases the chance that bees will transport pollen to conspecific plants on subsequent visits (Levin, 1978). For example, McEwan and Vamosi recently reported that within alpine plant communities, the colors of species that flower at similar times are more different from each other than predicted by chance (McEwan and Vamosi, 2010). This finding is consistent with a scenario wherein pollinators experience uncertainty in color signals and plants thus benefit by having flowers that are distinctly different from others in the same habitat.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way as in pollination, fruit characteristics such as size and color are associated to dispersal mode and dispersers (Wheelwright 1985;Flörchinger et al 2010;Galetti et al 2011;Cazetta et al 2012). Among the ecological processes shaping community structure (facilitation, competition and filtering), floral color diversity organizes alpine meadow communities through facilitation (McEwen & Vamosi 2010), and floral resource, size, color and shape are probably limiting the similarity among montane co-occurring species due to reproductive competition (Eaton et al 2012).…”
Section: Introductionmentioning
confidence: 99%